Development of Socio-Cultural Competence - N.R.Rustamova (Universitas Muhammadiyah Sidoarjo, 2022)
The purpose of this paper is to describe socio-cultural competence, its structure and components, as well as its importance in the modern world. We have studied and analyzed the points of view of various scientists, as well as psychological studies in this field. The topic is relevant indeed in the modern process of globalization. At the end of the article the conclusion of the reviewed materials and studies is also presente.